Proses Pembelajaran Daring Selama Pandemi Covid-19 di IAHN-TP Palangka Raya Perspektif Pendidikan Hindu - I Made Pustikayasa; I Nyoman Sidi Astawa; Ervantia Restulita L.Sigai (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2021)
The Covid-19 pandemic has had an impact on the world of education in Indonesia. The transformation of the face-to-face learning system in the classroom into an online learning system is a very important and urgent problem faced by the world of education. Since the beginning of the pandemic until now, the issue of learning online systems has been the focus of various studies. However, research on online learning at the Tampung Penyang State Hindu Institute (IAHN-TP) Palangka Raya is not yet available. Researchers are interested in studying online system learning at IAHN-TP Palangka Raya with a focus on problems how is the online system learning process during the Covid-19 pandemic at IAHN-TP Palangka Raya.The theory used to examine and describe the formulation of the research problem is the theory of phenomenology and the theory of the learning process. The research method used is a qualitative phenomenological research method with an emic approach. Data obtained from observations, interviews, and document studies. Furthermore, the data obtained are reduced, presented, and a conclusion is drawn.The data studied and analyzed using phenomenological theory and learning process theory show the following points, preparations made by lecturers in the online system learning process include the preparation of more detailed teaching materials, more interesting teaching techniques, the availability of learning tools, and the availability of internet networks. The implementation of learning is done virtual asynchronously and collaboratively synchronously by applying RQA and HOTS. Evaluation of learning outcomes is carried out online in the form of multiple choice of questions and self-analysis.Kata Kunci : learning process, online learning, learning during covid-19 pandemic